Delays in initiating rabies post-exposure prophylaxis among dog bite victims in Wakiso and Kampala districts, Uganda [version 3; peer review: 2 approved] - Gloria Bahizi; Samuel Majalija; SM Thumbi; Fredrick Makumbi; Stevens Kisaka (Open Research Africa)
Background   Although rabies in dog bite patients is preventable through timely initiation of post-exposure prophylaxis (PEP), a number of barriers to achieving PEP exist. This study investigated the delays to initiation of PEP among dog bite patients in the emergency departments of two PEP centers in Uganda. Methods A cross-sectional study was conducted among dog-bite patients that presented to two selected rabies PEP centers. A semi-structured questionnaire was used to collect data. Delay to receive PEP was defined as reporting for PEP beyond 24 hours after the bite event. Generalized linear models were used to calculate prevalence ratios and the 95% confidence intervals as a measure of association between delay and patient factors. Results Out of 376 participants, just over half (53.5%) were males. The majority of participants (54.0%) were 15 years or older and 28.5% had no formal education. Just over three-quarters (77.9%) had category II dog bite wounds. Nearly 40% delayed to receive PEP, and median (inter quartile range) lag time between bite event and seeking medical care of 18 (41) hours. Compared to education level of secondary or above, patients with no formal education (adj. PR=4.06, 95% CI: 2.69 -  6.10) or primary education (adj.PR=2.15, 95% CI: 1.37 -  3.35), belonging to the lowest socio-economic tertile as compared to the highest (adj.PR=1.58, 95% CI: 1.10 - 2.28), knowing the owner of the biting dog (adj.PR=1.30, 95% CI: 1.02 - 1.65) and having category II wounds (adj.PR=2.31, 95% CI: 1.43 - 3.71) were all associated with delayed presentation for PEP. Conclusions and recommendations Delays to receive PEP are common and are associated with poor level of education or low socio-economic status, knowledge of who the dog owner is and less severity of bite wounds. Seeking care irrespective of wound severity or knowledge of dog owner should be promoted.